Reckless girls [compact disc, unabridged] : a novel - Hawkins, Rachel, 1979- (Macmillan Audio, 2022)
When Lux McAllister and her boyfriend, Nico, are hired to sail two women to a remote island in the South Pacific, it seems like the opportunity of a lifetime. Stuck in a dead-end job in Hawaii, and longing to travel the world after a family tragedy, Lux is eager to climb on board The Susannah and set out on an adventure. She's also quick to bond with their passengers, college best friends Brittany and Amma. The two women say they want to travel off the beaten path. But like Lux, they may have other reasons to be seeking an escape. Shimmering on the horizon after days at sea, Meroe Island is every bit the paradise the foursome expects, despite a mysterious history of shipwrecks, cannibalism, and even rumors of murder. But what they don't expect is to discover another boat already anchored off Meroe's sandy beaches.